Strategic Team Management for Improved Engineering Performance: A Collaborative Perspective - Masduki Asbari; Dewiana Novitasari; Maya Monoarfa; Siswo Wardoyo (Motivaksi: Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
This study examines the influence of team characteristics (such as team efficacy) and environmental factors (such as emotional intelligence climate) on engineering team performance based on social cognitive theory (SCT). Data were collected through 157 questionnaires from engineering employees of a manufacturing company in Indonesia using random sampling method. Data analysis was conducted using SEM method with SmartPLS 4.0 software. The proposed model shows that work team planning acts as a mediator between team efficacy, emotional intelligence climate, and team performance. The findings provide an in-depth understanding of the factors that influence team performance in the context of the manufacturing industry. The results suggest that work team planning plays an important role in improving team performance through the effects of team efficacy and emotional intelligence climate. The practical implication of this study is the importance of company management to pay attention to both antecedents of team performance, both in terms of personal (efficacy) and environmental (emotional intelligence climate) in an effort to improve engineering team performance in a sustainable manner.